2010
DOI: 10.1590/s0034-737x2010000400015
|View full text |Cite
|
Sign up to set email alerts
|

Otimização de um protocolo para micropropagação da oliveira Ascolano 315

Abstract: Optimization of a protocol for the micropropagation of olive tree cv. Ascolano 315Micropropagation can be a viable technique for the multiplication of olive trees. The objective of this work was to induce multiplication in explants of olive tree. Nodal segments with 2 cm length, without leaves, derived from in vitro plantlets of cultivar Ascolano 315 were excised and inoculated in test tubes. The tubes contained 15 mL of OM (Olive medium) culture medium supplemented with 2 g L -1 of activated charcoal, 4 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
3
1
0
Order By: Relevance
“…Similar observation was also reported in olive cultivar 'MGSASC315' by VILLA et al (2010). The same variety (MGSASC315) included in our study the also perform well with 100ml L -1 of coconut water in agreement with the conclusion made by VILLA et al (2010). These authors also showed the positive effect of the coconut water in growth and development of the seedling during in vitro culture.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar observation was also reported in olive cultivar 'MGSASC315' by VILLA et al (2010). The same variety (MGSASC315) included in our study the also perform well with 100ml L -1 of coconut water in agreement with the conclusion made by VILLA et al (2010). These authors also showed the positive effect of the coconut water in growth and development of the seedling during in vitro culture.…”
Section: Resultssupporting
confidence: 92%
“…The strong and positive coefficient of determination presented in this work showed the general trend indicating the increase in coconut water dose from 0 to 100ml L -1 is positively associated with the increase in shoot length, number of leaves and number of internodes which indirectly leads us to conclude about the positive effect of coconut water in the seedling development and growth. Similar observation was also reported in olive cultivar 'MGSASC315' by VILLA et al (2010). The same variety (MGSASC315) included in our study the also perform well with 100ml L -1 of coconut water in agreement with the conclusion made by VILLA et al (2010).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The same pattern was seen in in vitro cultivated olive embryos, where CW supplementation enhanced the number of leaves but did not affect shoot length or other features (de Souza et al, 2013). The discrepancies in plantlet responses could be related to the CW treatment's reaction being relatively species-specific (Villa et al, 2010).…”
Section: Shoot Multiplication Of M Pudica In Response To Different Pl...supporting
confidence: 52%